ΤΟ ΠΑΛΙΟ ΝΟΣΟΚΟΜΕΙΟ (VETERA INFIRMARIA) ΣΤΗ ΡΟΔΟ: ΠΑΡΑΤΗΡΗΣΕΙΣ ΣΤΗΝ ΤΟΠΟΓΡΑΦΙΑ ΤΗΣ ΜΕΣΑΙΩΝΙΚΗΣ ΠΟΛΗΣ - ΚΑΡΑΣΑΒΒΑ ΤΣΙΛΙΓΓΙΡΗ, ΦΩΤΕΙΝΗ (Eoa kai Esperia, 1997)
The Order of the Hospital of St. John of Jerusalem was one of the MilitaryOrders founded during the First Crusade. Apart from fighting, its main dutieswere hospitaller and it had to maintain a great Hospital at their headquarters,first in Jerusalem and later in Acre, Cyprus, Rhodes, and Malta.The Order ruled Rhodes between 1310 and 1522. In 1483 their new Hospital,which was being built since 1439, was put to use. This Hospital, today theArcheological Museum of the town, succeeded another which from then onwas called the Vetera infirmarla in the Order's written documents.While the new Hospital is securely identified, the site of the Vetera infìrmarìais in fact unknown. It is generally believed that an extensively repaired buildingwhich today houses the Historical-Archeological Institute of Dodecannese canbe identified with it, on the grounds of some architectural characteristics survivingon its façade, and of the fact that part at least of the building was built in thefourteenth century. Some literary evidence from the fifteenth century, though,suggests otherwise.Very few buildings datable to the fourteenth century survive today in thetown of Rhodes. The topography of the medieval town itself wes extensivelyaltered in the later part of the Hospitaller rule, from 1480 to 1522 when theTurks of Suleyman the Magnificent occupied the island. Later, in the twentiethcentury, during Italian rule, a huge project of rehabilitating, rebuilding andexcavating the medieval town was realized, and the sixteenth century imagewas consolidated, while earlier evidence was concealed or altogether lost. Asbuildings dated to earlier phases of the history of the town are valuable aslandmarks for the study of the topography of these phases, it is important toidentify them securely before employing them in this manner. The Vetera infìrmarìais one such building, often appearing in the documents as a landmark.In the present paper, an effort is being made to locate the vetera infirmarlawithin the medieval town, using mainly documentary evidence. The possibilityof the simultaneous existence of two vetere infirmarle is discussed, one probablydestined for the sick brethren exclusively. The identification of the veterainfirmarla with the Historical-Archeological Institute cannot be excluded but itcannot be proven either. In any case, restituting a topography for the fourteenthandearly fifteenth century town of Rhodes is a complicated affair and should betaken up with caution.